A synthetic tumor necrosis factor-alpha agonist peptide enhances human polymorphonuclear leukocyte-mediated killing of Plasmodium falciparum in vitro and suppresses Plasmodium chabaudi infection in mice. - Kumaratilake, L M (1995)
A peptide corresponding to residues 70-80 of the TNF-alpha polypeptide was synthesized and shown to enhance human PMN-mediated killing of Plasmodium falciparum in vitro and reduced the Plasmodium chabaudi parasitemia in mice. Studies of the mechanism of action showed that the peptide, TNF(70-80), stimulated and primed PMN for an increased respiratory burst and release of granule constituents in response to a second agonist. The PMN-stimulatory activity of the peptide was inhibited by mAbs against the p55 and p75 TNF receptors and a TNF-neutralizing mAb. Analysis of PMN receptor expression showed that CR3 (CD18/CD11b) and Fc gamma RIII were upregulated by TNF(70-80), which was consistent with the peptide's ability to enhance parasite killing by PMN. The peptide, unlike TNF, did not increase the expression of adhesion molecules on endothelial cells and failed to promote binding of P. falciparum-infected erythrocytes to endothelial cells. TNF(70-80) also inhibited the TNF-induced increase in adhesion of P. falciparum-infected erythrocytes to endothelial cells. The results demonstrate that the host-protective effects of TNF can be retained while toxic effects are eliminated using a selected, characterized subunit of the cytokine.